Case formulation with children and adolescents - Manassis, Katharina (New York ; London : The Guilford Press, 2014)
"Highly practical and accessible, this book shows how to synthesize complex information about child and adolescent mental health problems into clinically useful case formulations that complement diagnosis. Provided are strategies and tools for analyzing the biological, psychological, social, cultural, and developmental factors that may be contributing to a child's or adolescent's difficulties (ages 4-18). Numerous case examples illustrate the steps in crafting a comprehensive formulation and using it to plan effective, individualized treatment. Helpful reproducible forms can be downloaded and printed in a convenient 8 1/2" x 11" size"--
Includes bibliographical references (pages 229-235) and index.
Keywords: Psychiatry -- Case formulation; Interviewing in child psychiatry; Interviewing in adolescent psychiatry; Child psychiatry -- Differential therapeutics; PSYCHOLOGY / Psychotherapy / Child & Adolescent; MEDICAL / Psychiatry / Child & Adolescent; SOCIAL SCIENCE / Social Work; EDUCATION / Counseling / General